Faktor Minat Non Muslim Menjadi Nasabah di Bank Syariah - Lely Ana Ferawati Ekaningsih; Risma Eka Riana (Proceedings of Annual Conference for Muslim Scholars, 2018)
The purpose of this study is to determine the factors that influence non-Muslim interest to be customers in Bank Syariah. This type of explanatory research used to test the relationship between hypothesized variables. The variables used are five independent variables, namely Location (X1), Service (X2), Reputation (X3), Promotion (X4) and Profit Sharing (X5). The dependent variable is non-Muslim interest to be a customer in Bank Syariah (Y). Location of research at BRI Sharia Branch Office of Banyuwangi Sub-district. Sampling census technique is Census Sampling that is all non-Muslim customer in BRI Syariah Branch Office of Banyuwangi Sub-district as many as 13 people. The most powerful correlation, 84.9% is location variable (X1), indicating if customers consider the location of BRI Syariah easily accessible. The second strongest correlation of 71% is reputation (X3), indicating if a good and reliable Reputation is the source of competitive advantage of a bank. The third correlation of 67.4%, is promotion, this indicates that the promotion has been done by BRI Sharia is already good and acceptable by the community, especially for non-Muslim community. While the variables that do not have correlation to the interest is the service of 18.2% and profit sharing 4.3%, indicate if non-Muslim interests become customers not on service and profit sharing.